Antifungal activity of the extracts and fractions of dahlia tuber (Dahlia variabilis) against pathogenic skin fungi - SARYONO SARYONO; NOVA OCTARINA; YUHARMEN YUHARMEN; NOVA WAHYU PRATIWI; AULIA ARDHI (Smujo International, 2017)
Saryono, Octarina N, Yuharmen, Pratiwi NW, Ardhi A. 2017. Antifungal activity of the extracts and fractions of dahlia tuber (Dahlia variabilis) against pathogenic skin fungi. Nusantara Bioscience 9: 146-151. Dahlia plant (Dahlia variabilis) can be easily found in the highlands in Indonesia and its tuber has been reported to have some bioactive compounds which are potential to be utilized as an antimicrobial agent. This study aimed to determine antifungal activity and minimum inhibitory concentration (MIC) of n-hexane and methanol extracts and fractions of red-flowered dahlia tubers against pathogenic skin fungi Candida albicans and Microsporum gypseum using disc diffusion method. The n-hexane and methanol extracts and fractions of dahlia tuber showed their antifungal activity against C. albicans and M. gypseum, with the larger activity, was found in both extracts and fractions of methanol. The best fractions of n-hexane and methanol were chosen and determined their minimum inhibitory concentration; which the F5 n-hexane fraction and the F2 methanol fraction gave the MIC of 1.50% and 0.50% against C. albicans respectively, whereas both F1 n-hexane and F2 methanol fraction gave the MIC of 0.50% against M. gypseum. The high antifungal activity of F2 of methanol extract against C. albicans and M. gypseum allowed this fraction to be utilized as a medicinal drug for candidiasis and other fungal skin infections.